A simple indirect colorimetric assay for measuring mitochondrial energy metabolism based on uncoupling sensitivity - Herst, Patries M. (Biochem Biophys Rep, 2020)
PURPOSE: Cancer cells rapidly adjust their balance between glycolytic and mitochondrial ATP production in response to changes in their microenvironment and to treatments like radiation and chemotherapy. Reliable, simple, high throughput assays that measure the levels of mitochondrial energy metabolism in cells are useful determinants of treatment effects. Mitochondrial metabolism is routinely determined by measuring the rate of oxygen consumption (OCR). We have previously shown that indirect inhibition of plasma membrane electron transport (PMET) by the mitochondrial uncoupler, FCCP, may also be a reliable measure of mitochondrial energy metabolism. Here, we aimed to validate these earlier findings by exploring the relationship between stimulation of oxygen consumption by FCCP and inhibition of PMET. METHODS: We measured PMET by reduction of the cell impermeable tetrazolium salt WST-1/PMS. We characterised the effect of different growth conditions on the extent of PMET inhibition by FCCP. Next, we compared FCCP-mediated PMET inhibition with FCCP-mediated stimulation of OCR using the Seahorse XF96e flux analyser, in a panel of cancer cell lines. RESULTS: We found a strong inverse correlation between stimulation of OCR and PMET inhibition by FCCP. PMET and OCR were much more severely affected by FCCP in cells that rely on mitochondrial energy production than in cells with a more glycolytic phenotype. CONCLUSION: Indirect inhibition of PMET by FCCP is a reliable, simple and inexpensive high throughput assay to determine the level of mitochondrial energy metabolism in cancer cells.